Financial feasibility assessment of adopting active controlled atmosphere containers for exporting highly perishable fruits during COVID-19: case of Taiwanese atemoya. Issue 3 (24th December 2021) - Huang, Wen-Hung; Dy, Kenneth Bicol; Chang, Ching-Cheng; Hsu, Shih-Hsun
Abstract : Purpose: This study deals with attenuating the risk of relying on a single export market, which was heightened by the outbreak of the COVID-19 pandemic. It focuses on Taiwanese atemoya (a fruit with short storage life) and the adoption of active controlled atmosphere (CA) containers, a new technology which lengthens storage time for other export markets. This study looks at the financial feasibility of the technology's first ever use in atemoya exports. Design/methodology/approach: Apart from the standard financial assessment tools—like net present value (NPV), internal rate of return (IRR), benefit-cost ratio (BCR) and payback period (PBP)—this study calibrated five different scenarios based on data gathered from relevant market agents including suppliers, exporters, customs brokers and technology developer. Findings: Due to the high profit margin and low investment cost, the use of active CA containers for long-haul exports of this highly perishable fruit is found both technically and financially feasible, despite the generally higher operational cost during the pandemic. Research limitations/implications: This study looked at three specific export markets: Malaysia, Dubai and Canada. Results here may lack generalizability in other markets, although it is believed that slight deviations would not invalidate the conclusions of this research because short, medium and long distances were all covered therein. Originality/value: This paper studies the first time that active CA is used for export of atemoyas to expand existing markets.